ANALISIS KINERJA BAWASLU KOTA BENGKULU DALAM PENYELESAIAN LAPORAN SENGKETA - Apriansyah Apriansyah; Rosidin Rosidin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
Regional head elections are a means of realizing people’s sovereignty in Indonesia’s democratic system, and therefore must be conducted in a fair, honest, and transparent manner. In the electoral process, disputes between parties often arise and require the role of the Election Supervisory Body (Bawaslu) as both a supervisory institution and a dispute resolution body. This study aims to analyze the performance of Bawaslu of Bengkulu City in resolving dispute reports involving Bengkulu mayoral candidate Ariyono Gumay. This research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, while data validity was tested using triangulation. Performance analysis was conducted based on indicators of quality, quantity, and cooperation. The results show that the performance of Bawaslu of Bengkulu City in resolving disputes is relatively good. In terms of quality, Bawaslu has carried out the dispute resolution process in accordance with applicable procedures and regulations. In terms of quantity, dispute reports were handled systematically and in a timely manner. In terms of cooperation, Bawaslu established coordination with the KPU, law enforcement agencies, and the community. However, greater public outreach is still needed regarding electoral dispute resolution mechanisms. Overall, Bawaslu’s performance contributes to maintaining the integrity and credibility of the regional election process in Bengkulu City. Keywords: performance, Bawaslu, electoral disputes, regional elections, election supervision.